A highly efficient and robust Cu/SiO2 catalyst prepared by the ammonia evaporation hydrothermal method for glycerol hydrogenolysis to 1, 2-propanediol. Issue 2 (11th November 2014) - Zhu, Shanhui; Gao, Xiaoqing; Zhu, Yulei; Fan, Weibin; Wang, Jianguo; Li, Yongwang
Abstract : The Cu/SiO2 catalyst prepared by the ammonia evaporation hydrothermal method presented unprecedented stability (300 h) for glycerol hydrogenolysis to 1, 2-propanediol. Abstract : A highly efficient and robust Cu/SiO2 catalyst from a pure-phase copper phyllosilicate precursor was successfully fabricated by the ammonia evaporation hydrothermal (AEH) method. The impregnation (IM) Cu/SiO2 catalyst was prepared for comparison. The structure, morphologies, thermal stability and surface chemical state of these catalysts were comprehensively characterized by ICP, BET, XRD ( in situ XRD), N2 O chemisorption, H2 -TPR, IR and Raman spectroscopy, TEM and XPS. Compared to the IM sample, the AEH catalyst was exceedingly highly active and stable (300 h) for glycerol hydrogenolysis to 1, 2-propanediol. The unprecedented catalytic performance was attributed to the strong interaction between Cu and SiO2 species derived from copper phyllosilicate, well-dispersed Cu nanoparticles and the cooperative effect of Cu 0 and Cu + . Moreover, active Cu 0 species were identified as the primary active sites for glycerol hydrogenolysis, as corroborated by the strong correlation between 1, 2-propanediol yield and Cu surface area.